The States and Problems Related to the Administration of Small-sized Schools under the Loei Primary Education Service Area Office 2 - พรมมาศ, สุกัญญา; ศิริเกษ, บุญช่วย; คำมา, ภารดี (Journal of Roi Et Rajabhat University, 2016)
This research aimed to 1) investigate the states and problems in administration of smallsized schools under the Loei Primary Educational Service Area Office 2, 2) compare the states and problems in administration of small-sized schools under the Loei Primary Educational Service Area Office 2 classified by gender, position, education qualification, and work experience of the sample. 29 school administrators and 240 teachers were selected as the research sample. The research instrument was a rating scale questionnaire. The data were analyzed using frequencies, percentages, means, and standard deviations. The research hypotheses were tested by t-test and Ftest. The study found that 1. The states in administration of smallsized schools under the Loei Primary Educational Service Area Office 2 were at a high level in all aspects. The aspects rated from the highest to the lowest level were the academic aspect, general administration and budget administration respectively. In terms of problems in school administration, the aspects rated from the highest to the lowest were general administration, personnel administration and academic administration respectively. 2. The lelvel of states in administration of small-sized schools under the Loei Primary Educational Service Area Office 2 perceived by the respondents classified by their educational qualification and their work experience was not different. There were also no any significant differences in terms of level of problems concerning school administration perceived by the respondents classified by their position, their educational qualification and their work experience.